Fermentation of Microalgae as a Platform for Naturally Encapsulated Oil Powders: Characterization of a High-Oleic Algal Powder Ingredient - Walter Rakitsky; Leon Parker; Kevin Ward; Thomas Pilarski; James Price; Mona Correa; Roberta Miller; Veronica Benites; Dino Athanasiadis; Bryce Doherty; Lucy Edy; Jon Wittenberg; et al. (Microorganisms, 2025)
Powdered oil ingredients are widely used across food, nutrition, and personal care industries, but they are typically produced through encapsulation technologies that involve multiple additives and stabilizers. These systems can compromise oxidative stability, clean-label compliance, and functional performance. Here, we present the development and characterization of a novel high-oleic algal powder (HOAP) produced from a heterotrophically fermented microalgae. The production strain was developed through classical mutagenesis to enhance oleic acid and lipid accumulation. Three independent fermentation batches at a 20 L scale demonstrated strong reproducibility in key metrics, including dried-cell weight (210.0 g per L on average, CV% = 0.7), oil content (62.0% of DCW on average, CV% = 2.0), and oleic acid (88.8% of total fatty acids on average, CV% = 0.1). HOAP exhibited a favorable nutritional profile (e.g., high monounsaturated fat and fiber, low sugar and moisture) and good oxidative stability under ambient and accelerated storage conditions. Microbiological analyses confirmed compliance with food-grade standards, and in silico allergenicity screening revealed no clinically relevant homologs. Unlike traditional oil powders, HOAP does not require encapsulation and retains oil within a natural protein–fiber matrix, offering both functional and clean-labeling advantages. Its compositional attributes and stability profile support potential use in food, nutrition, and the delivery of bioactive nutrients. These findings establish HOAP as a next generation of oil powder ingredients with broad application potential.